Global perspectives on women in management and the labor markets - Pereira, Elisabeth T. 1970-; Paoloni, Paola (IGI Global, 2019)
"This book focuses on the existent inequalities, the gender gap, and women's role in management and in the labor markets. It also examines the point of convergence among entrepreneurship organizations, relationship, creativity and culture from a gender perspective"--